Getting a grip on the resilience to blur: The impact of simulated vision loss on a visually guided combat sports interaction - Krabben, K.; Mann, D. L.; van Helden, A.; Kalisvaart, Y.; Fortin-Guichard, D.; van der Kamp, J.; Savelsbergh, G. J. P. (Psychology of Sport and Exercise, 2021)
Research has shown that performance in highly visually demanding sports can be resilient to substantial levels of blur. This raises the question whether the need for high visual clarity might be reduced even more in less visually demanding sports such as combat sports, where athletes compete at relatively close distances. The aim of this study was to examine the resilience to blur in the grip fighting phase of judo as an exemplar of a visually guided combat sports task. The results were particularly relevant for the purposes of Paralympic judo for athletes with vision impairment (VI judo), because athletes are currently allowed to compete with a visual acuity (VA) of 1.0 logMAR or worse (i.e., 6/60 or 20/200 vision), suggesting this is the presumed level of impairment that decreases performance in able-sighted judo. We let 28 able-sighted judo athletes compete in pairs in a series of grip fighting tasks under increasing levels of simulated vision impairment. Visual function was tested in each condition by measuring VA and contrast sensitivity (CS). We found that VA was a better predictor than CS of grip fighting performance. VA needed to be reduced to at least 1.3 logMAR before a decrease in performance was found, with approximately twice as much blur needed to be applied when compared to visually demanding tasks such as cricket batting, but less than what has been found in static tasks such as basketball free-throw shooting and golf putting. These findings hold implications for VI judo regulations, suggesting that a more severe degree of impairment should be required to participate than is currently the case. Highlights: • Grip fighting performance of able-sighted judo athletes is resilient to severe blur. • Visual acuity needs to be reduced to at least 1.3 logMAR to impact performance. • Visual acuity better predicts grip fighting performance than contrast sensitivity. • Change is recommended with more impairment required to be eligible for Paralympic judo.